Euro Area Government Bonds—Integration and Fragmentation During the Sovereign Debt Crisis - Michael Ehrmann; Marcel Fratzscher (Bank of Canada, 2015)
The paper analyzes the integration of euro area sovereign bond markets during the European sovereign debt crisis. It tests for contagion (i.e., an intensification in the transmission of shocks across countries), fragmentation (a reduction in spillovers) and flight-to-quality patterns, exploiting the heteroskedasticity of intraday changes in bond yields for identification. The paper finds that euro area government bond markets were well integrated prior to the crisis, but saw a substantial fragmentation from 2010 onward. Flight to quality was present at the height of the crisis, but has largely dissipated after the European Central Bank's (ECB's) announcement of its Outright Monetary Transactions (OMT) program in 2012. At the same time, Italy and Spain became more interdependent after the OMT announcement, providing our only evidence of contagion. While this suggests that countries have been effectively ring-fenced, and Italy and Spain benefited from the joint reduction in yields following the OMT announcement, the high current degree of fragmentation poses difficult challenges for policy-makers, since it leads to an unequal transmission of the ECB's monetary policy to the various countries.
Keywords: F3; E5; G15; 330; Asset pricing; Financial markets; Interest rates; International financial markets